2004
DOI: 10.1038/nature02943
|View full text |Cite
|
Sign up to set email alerts
|

Control of ion selectivity in potassium channels by electrostatic and dynamic properties of carbonyl ligands

Abstract: Potassium channels are essential for maintaining a normal ionic balance across cell membranes. Central to this function is the ability of such channels to support transmembrane ion conduction at nearly diffusion-limited rates while discriminating for K+ over Na+ by more than a thousand-fold. This selectivity arises because the transfer of the K+ ion into the channel pore is energetically favoured, a feature commonly attributed to a structurally precise fit between the K+ ion and carbonyl groups lining the rigi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

53
720
5
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 553 publications
(779 citation statements)
references
References 30 publications
53
720
5
1
Order By: Relevance
“…However, recent molecular dynamics (MD) simulation studies performed an analysis of cation-oxygen correlation functions in the KcsA selectivity filter, which suggested that although its most central canonical binding site coordinates K ϩ or Na ϩ with eight carbonyl oxygen atoms, the dynamic carbonyl ligands ''collapse'' around bound Na ϩ , providing the expected coordination radius for this smaller ion (5). This observation (among others) led to the hypothesis that the electrostatic nature of carbonyl groups imparts K ϩ -selective ion binding by providing a build-up of unfavorable strain energy via carbonyl-carbonyl repulsion upon coordinating Na ϩ (5, 9, 10).…”
Section: [1]mentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent molecular dynamics (MD) simulation studies performed an analysis of cation-oxygen correlation functions in the KcsA selectivity filter, which suggested that although its most central canonical binding site coordinates K ϩ or Na ϩ with eight carbonyl oxygen atoms, the dynamic carbonyl ligands ''collapse'' around bound Na ϩ , providing the expected coordination radius for this smaller ion (5). This observation (among others) led to the hypothesis that the electrostatic nature of carbonyl groups imparts K ϩ -selective ion binding by providing a build-up of unfavorable strain energy via carbonyl-carbonyl repulsion upon coordinating Na ϩ (5, 9, 10).…”
Section: [1]mentioning
confidence: 99%
“…Finally, replacement of the carbonyl ligands in an 8-coordinated simplified binding site by TIP3P model water molecules, each with a dipole moment of ϳ2.35 D (12), yielded an absence of selectivity (9,10). These findings appear to imply the following: (i) binding sites using carbonyl moieties, effectively possessing a dipole in the range of 2.5-4.5 D, are uniquely suited to select K ϩ over Na ϩ ; (ii) hydration of a cation in a binding site causes loss of K ϩ selectivity because the field strength of a water molecule is small enough such that the ligand-ligand repulsion in the coordination complex resulting from Na ϩ binding is reduced; and (iii) external restraints from the protein are not required for selective binding of K ϩ by carbonyl ligands (5,9,10). The surprising ramifications of the carbonyl-repulsion hypothesis spurred us to design a few simple computational experiments to address the issues (i-iii) above.…”
Section: [1]mentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that S177W decreases filter flexibility, consistent with a theory that a rigid filter cannot discriminate between ions (19). Alternatively, S177W could have reduced K ϩ selectivity by displacing Y157, a critical site for KcsA selectivity (19). N184D (green residue in Fig.…”
Section: Effect Of the M2 Helix Mutations On The Geometry Of The Selementioning
confidence: 99%
“…For example quinolone-based ligands do not compete for the cofactor of binding site of alcohol dehydrogenase like glyceraldehyde phosphate dehydrogenase (GAPDH) due to unfavorable intrinsic electrostatics and hydrogen bonding (Waingeh et al, 2013). Similarly, the discrimination between K + and Na + by the narrowing potassium channel KscA is due to the intrinsic electrostatics and coordination between ions and carbonyl groups (Noskov et al, 2004). In general a single molecular determinant cannot usually explain the high affinity or selectivity in functional protein complexes (Astorga et al, 2012).…”
Section: Discussionmentioning
confidence: 99%